Precursor for high-compaction polyanionic sodium ion battery positive electrode material and preparation method thereof

By preparing the MxPOy·mH2O precursor, the problems of insoluble solid particles, phase separation and poor density in the preparation of the positive electrode material of polyanionic sodium ion battery were solved, and materials with high compaction density, high phase purity and excellent electrochemical performance were achieved.

CN119560557AActive Publication Date: 2025-03-04CHENGDU JIASAN ENERGY TECHNOLOGY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411604335.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-04
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

During the preparation of existing polyanionic sodium ion battery positive electrode materials, solid particles such as high crystalline FePO4 and FeC2O4 are difficult to completely dissolve, resulting in phase separation, affecting the performance of electrochemical performance, and poor density during sintering and low compaction density.

Method used

A transition metal source is reacted with an organic acid to form a water-soluble transition metal ions, and mixed with a phosphorus source through oxidation of an oxidizing agent to form a MxPOy·mH2O precursor. The precursor is prepared by temperature-controlled reaction, preoxidation, drying and high-temperature calcination, forming a long-range disordered structure in which transition metal ions and phosphate/pyrophosphate are meshed with each other.

Benefits of technology

A positive electrode material of polyanionic sodium ion battery with high compaction density and high phase purity is achieved, with excellent electrochemical performance and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560557A_ABST
    Figure CN119560557A_ABST
Patent Text Reader

Abstract

The invention discloses a precursor for a high-compaction polyanionic sodium ion battery positive electrode material and a preparation method thereof, the chemical general formula of the precursor is MxPOy.mH2O, M is a transition metal element Fe and / or Mn, and the value range relation of x, y and m is 0.4 lt; xlt; y is equal to 3.5 / 3.75; m > = 0. The precursor for the high-compaction polyanionic sodium ion battery positive electrode material and the preparation method of the precursor have the characteristics of high compaction density, high phase purity, capability of meeting different system requirements, excellent electrochemical performance and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a precursor for a high-density polyanion sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] Polyanion-type sodium ion battery positive electrode materials include sodium iron pyrophosphate, sodium iron pyrophosphate, sodium vanadium phosphate, sodium vanadium fluorophosphate, etc., which are three-dimensional framework structures formed by alkali metal tetrahedrons, transition metal tetrahedrons / octahedrons, and anion tetrahedron / trihedron groups arranged in a common point / surface / line manner. They have excellent structural stability, thermodynamic stability, cycle stability, rate performance, etc., and have been widely favored by the market.

[0003] At present, commercially available materials such as sodium iron pyrophosphate are all synthesized using the solid-phase method, which uses highly crystalline anhydrous FePO4, FeC2O4, etc. as transition metal precursor sources, combined with water-soluble sodium sources, phosphorus sources and carbon sources, and the preparation of the material is achieved through grinding, mixing, spray drying, sintering and other processes.

[0004] However, highly crystalline solids such as FePO4 and FeC2O4 are difficult to completely dissolve during the grinding process. They are often suspended in the solution as solid particles of tens to hundreds of nanometers. These solid particles contain tens of thousands of atoms. From a local perspective, the sodium, transition metals and phosphorus elements in the slurry are difficult to mix evenly, which can easily lead to phase separation during the sintering process, affecting the electrochemical properties of the material.

[0005] At the same time, highly crystalline solid particles such as anhydrous FePO₄ and FeC₂O₄ are difficult to melt and agglomerate during the sintering process, resulting in a large number of residual pores within the product particles, affecting the material's compactness and leading to a low compaction density. Therefore, in order to obtain polyanionic materials with high phase purity, high compaction density, and low manufacturing process costs, it is necessary to develop suitable precursors for them. Summary of the Invention

[0006] The purpose of the present invention is to provide a precursor for a high-density polyanion sodium ion battery positive electrode material and a preparation method thereof, which has the characteristics of high compaction density, high phase purity, meeting the requirements of different systems, excellent electrochemical performance and low cost.

[0007] The present invention can be achieved through the following technical solutions: The present invention discloses a precursor for a high-density polyanion type sodium ion battery cathode material, the precursor having a general chemical formula of M x PO y mH2O, where M is the transition metal element Fe and / or Mn, and the range of values ​​of x, y, and m is 0.4 <x<1,y=3.5 / 3.75;m≥0。

[0008] Another aspect of the present invention is to provide a method for preparing a precursor for a high-density polyanion sodium ion battery positive electrode material, comprising the following steps: S1. Preparation of precursor solution: wet mixing the transition metal source and the organic acid, and reacting them under controlled temperature to generate a precursor solution; S2. Preparation of a pre-oxidation precursor solution: adding an oxidant to the above solution to oxidize the divalent metal ions in the solution into trivalent metal ions to generate a pre-oxidation precursor solution; S3. Preparation of an ionic mixture: adding a phosphorus source to the above-mentioned pre-oxidation precursor solution to form a uniform ionic mixture; S4. Preparation of precursor powder: drying the above ionic mixture to remove moisture to obtain dry precursor powder; S5. High temperature calcination: calcining the above precursor powder at high temperature to remove the volatile components in the powder and to make the phosphate radical undergo polycondensation reaction. After cooling naturally, M is obtained. x PO y mH2O material.

[0009] The precursor chemical formula of the present invention is M x PO y mH2O, which reacts a transition metal source with an organic acid to form water-soluble transition metal ions. This is then oxidized with an oxidizing agent and mixed with a phosphorus source. After evaporation and desolvation, it is further calcined to deoxidize and pyrophosphorylate the phosphate, ultimately forming the desired precursor material. This precursor has a long-range disordered structure formed by the interlocking of transition metal ions and phosphate / pyrophosphate. Its small particle size and lack of crystallinity make it extremely easy to grind and disperse. When mixed with other components, it exhibits good uniformity. The resulting sintered material has high phase purity and compacted density, and exhibits excellent electrochemical properties.

[0010] Furthermore, in step S1, the molar ratio of the transition metal source to the organic acid is 1:5-15; the purpose is to ensure that there are sufficient hydrogen ions in the solution to dissolve the transition metal source, so that it is completely dissolved in the solution in the form of ions. When the molar ratio of the transition metal source to the organic acid is lower than 1:5, the transition metal source cannot be effectively dissolved.

[0011] Furthermore, in step S1, the temperature of the temperature-controlled reaction is 70-120°C. When the temperature is lower than 70°C, the transition metal oxide cannot be effectively dissolved, while when the temperature is higher than 120°C, the reaction speed is too fast, the energy consumption is high, there are safety risks and the cost investment is large.

[0012] Furthermore, in step S2, the amount of oxidant added is 1-2.5 times the molar amount of the transition metal ions in the solution. When the molar amount of the oxidant is less than 1 times the transition metal ions, the excess metal ions in the solution cannot effectively undergo oxidation reaction, and when the molar amount of the oxidant is higher than 2.5 times the transition metal ions, the residual oxidant will increase the production cost.

[0013] Furthermore, in step S5, the temperature of high temperature calcination is 150-400°C; its purpose is to decompose the volatile carbon, oxygen, hydrogen and other components in the precursor, and at the same time, to condense part of the phosphate into pyrophosphate under the catalysis of hydrogen ions, and finally form M x PO y ·mH2O material; when the temperature is lower than 150°C, the volatile components in the precursor powder are difficult to completely decompose and remove, and the phosphate group is also difficult to condense to form pyrophosphate; when the temperature is higher than 400°C, the MxPOy·mH2O material transitions to melt and crystallize, forming dense and hard block particles, which affects the synthesis of subsequent materials.

[0014] Furthermore, in step S2, the oxidant is one or more of hydrogen peroxide, peracetic acid, and oxygen, which can oxidize transition metal ions. The purpose is to oxidize the divalent metal ions in the solution so that they can undergo a reduction reaction in the subsequent preparation of polyanion materials and form a better framework structure during the high temperature process.

[0015] Furthermore, in step S1, the transition metal source is an iron source and / or a manganese source, the iron source is one or more of elemental iron, red iron oxide, ferrous oxide, ferric oxide, ferric hydroxide, ferrous oxyhydroxide, ferrous hydroxide, ferric citrate, and ferric oxalate, and the manganese source is one or more of elemental manganese, manganese monoxide, manganese dioxide, manganese trioxide, manganese tetraoxide, manganese oxalate, manganous hydroxide, manganous anhydride, manganic anhydride, and permanganic anhydride; and the organic acid is one or more of formic acid, acetic acid, citric acid, malic acid, ascorbic acid, tartaric acid, and salicylic acid.

[0016] Furthermore, in step S3, the phosphorus source is one or more of phosphoric acid, pyrophosphoric acid, metaphosphoric acid, and polyphosphoric acid.

[0017] Furthermore, in step S4, the drying method is one or more of flash drying, spray drying, high temperature cracking, freeze drying, forced air drying, and natural evaporation.

[0018] The present invention provides a precursor for a high-density polyanion sodium ion battery cathode material and a preparation method thereof, which has the following beneficial effects: First, the compaction density is high, M x PO yAfter the mH2O precursor and the additional sodium source are ground and mixed evenly, the elements are bonded to each other. The distance between ions is short, and crystal nuclei can be formed in situ without long-distance diffusion. They continue to diffuse and grow along the epitaxy to form dense large-grained single crystals. There are fewer pores between the crystals, and the compaction density is greatly improved. Second, high phase purity: M x PO y The transition metals, phosphates, or pyrophosphates in the mH2O precursor are mixed more evenly. When using it as a precursor to prepare polyanionic materials, only the required water-soluble sodium source needs to be supplemented. This source will penetrate into the material through the pores in the precursor, achieving uniform mixing between the elements and preparing high-phase-purity materials. Third, meet the needs of different systems: M x PO y The element ratio of the mH2O precursor is y=3.5 / 3.75. This means that the precursor can be used to prepare pure pyrophosphate precursors or phosphate / pyrophosphate composite precursors by adjusting pH and element content. This precursor is compatible with the structural design requirements of existing polyanion systems (including ferric pyrophosphate / sodium manganese, ferric pyrophosphate / sodium manganese, and non-stoichiometric composite ferric phosphate / sodium manganese), enabling controllable regulation of the structure of high-purity phase materials. Fourth, excellent electrochemical performance: due to M x PO y The mH2O precursor can achieve uniform mixing between elements, so the material prepared from it has the characteristics of high crystallinity and high phase purity. The elements in the structure are arranged regularly and orderly, and the energy barrier for sodium ion deintercalation is low, which makes the material have high charge and discharge capacity and excellent rate performance. Fifth, low cost: M x PO y The mH2O precursor has a low sintering temperature and weak crystallinity. The bonding energy between the transition metal and phosphate / pyrophosphate in its structure is weak, so when preparing polyanionic materials, it does not require long-term grinding to achieve the purpose of uniform mixing. This greatly reduces the front-end grinding energy consumption and equipment investment, effectively reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 For the application of Example 1.Fe 0.7275 PO 3.75 Preparation of 0.01H2O precursor and Na4Fe 2.91 (PO4)2P2O7 material SEM; Figure 2 Preparation of Na4Fe from anhydrous FePO4 precursor in Comparative Example 1 2.91 SEM of (PO4)2P2O7 material. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below with reference to embodiments.

[0021] The present invention discloses a precursor for a high-density polyanion type sodium ion battery cathode material, the precursor having a general chemical formula of M x PO y mH2O, where M is the transition metal element Fe and / or Mn, and the range of values ​​of x, y, and m is 0.4 <x<1,y=3.5 / 3.75;m≥0。

[0022] Another aspect of the present invention is to provide a method for preparing a precursor for a high-density polyanion sodium ion battery positive electrode material, comprising the following steps: S1. Preparation of precursor solution: wet mixing the transition metal source and the organic acid, and reacting them under controlled temperature to generate a precursor solution; S2. Preparation of a pre-oxidation precursor solution: adding an oxidant to the above solution to oxidize the divalent metal ions in the solution into trivalent metal ions to generate a pre-oxidation precursor solution; S3. Preparation of an ionic mixture: adding a phosphorus source to the above-mentioned pre-oxidation precursor solution to form a uniform ionic mixture; S4. Preparation of precursor powder: drying the above ionic mixture to remove moisture to obtain dry precursor powder; S5, high temperature calcination: calcining the above precursor powder at high temperature, and then cooling naturally to obtain M x PO y mH2O material.

[0023] Furthermore, in step S1, the molar ratio of the transition metal source to the organic acid is 1:5-15.

[0024] Furthermore, in step S1, the temperature of the temperature-controlled reaction is 70-120°C.

[0025] Furthermore, in step S2, the amount of the oxidant added is 1-2.5 times the molar amount of the transition metal ions in the solution.

[0026] Furthermore, in step S5, the temperature of high-temperature calcination is 150-400°C.

[0027] Furthermore, in step S2, the oxidant is one or more of hydrogen peroxide, peracetic acid, and oxygen.

[0028] Furthermore, in step S1, the transition metal source is an iron source and / or a manganese source, the iron source is one or more of elemental iron, red iron oxide, ferrous oxide, ferric oxide, ferric hydroxide, ferrous oxyhydroxide, ferrous hydroxide, ferric citrate, and ferric oxalate, and the manganese source is one or more of elemental manganese, manganese monoxide, manganese dioxide, manganese trioxide, manganese tetraoxide, manganese oxalate, manganous hydroxide, manganous anhydride, manganic anhydride, and permanganic anhydride; and the organic acid is one or more of formic acid, acetic acid, citric acid, malic acid, ascorbic acid, tartaric acid, and salicylic acid.

[0029] Furthermore, in step S3, the phosphorus source is one or more of phosphoric acid, pyrophosphoric acid, metaphosphoric acid, and polyphosphoric acid.

[0030] Furthermore, in step S4, the drying method is one or more of flash drying, spray drying, high temperature cracking, freeze drying, forced air drying, and natural evaporation.

[0031] Example 1 This embodiment relates to a precursor for a high-density polyanion sodium ion battery positive electrode material. The precursor has the general chemical formula M x PO y mH2O, where M is the transition metal element Fe, and the range of values ​​of x, y, and m is 0.4 <x<1,y=3.5 / 3.75;m≥0。

[0032] The precursor was prepared by the following method: S1. Preparation of a precursor solution: A transition metal source and an organic acid are wet-mixed in a molar ratio of 1:15 and reacted at 100°C to form a precursor solution. Specifically, the transition metal source is an iron source, which may be ferric hydroxide, ferric oxyhydroxide, ferrous hydroxide, ferric citrate, or ferric oxalate; and the organic acid is formic acid, acetic acid, citric acid, or malic acid.

[0033] S2. Preparation of a pre-oxidation precursor solution: An oxidant is added to the above solution to oxidize the divalent metal ions in the solution to trivalent metal ions, thereby generating a pre-oxidation precursor solution. Specifically, the amount of the oxidant added is 1.5 times the molar amount of the transition metal ions in the solution; the oxidant is hydrogen peroxide or peracetic acid.

[0034] S3. Preparation of an ionic mixture: Add a phosphorus source to the above-mentioned pre-oxidation precursor solution to form a uniform ionic mixture. Specifically, the phosphorus source is phosphoric acid, pyrophosphoric acid, or metaphosphoric acid.

[0035] S4. Preparation of precursor powder: Dry the ionic mixture to remove moisture and obtain dry precursor powder. Specifically, the drying method is flash drying or spray drying.

[0036] S5, high temperature calcination: calcining the above precursor powder at high temperature, and then cooling naturally to obtain M x PO y mH2O material. Specifically, the high-temperature calcination temperature is 150°C.

[0037] Example 2 This embodiment relates to a precursor for a high-density polyanion sodium ion battery positive electrode material. The precursor has the general chemical formula M x PO y mH2O, where M is the transition metal element Mn, and the range of values ​​of x, y, and m is 0.4 <x<1,y=3.5 / 3.75;m≥0。

[0038] The precursor was prepared by the following method: S1. Preparation of a precursor solution: A transition metal source and an organic acid are wet-mixed in a molar ratio of 1:10 and reacted at 120°C to form a precursor solution. Specifically, the transition metal source is a manganese source, such as trimanganese tetraoxide, manganese oxalate, manganese hydroxide, manganous anhydride, manganic anhydride, or permanganic anhydride; and the organic acid is formic acid, acetic acid, or salicylic acid.

[0039] S2. Preparation of a pre-oxidation precursor solution: An oxidant is added to the above solution to oxidize the divalent metal ions in the solution to trivalent metal ions, thereby generating a pre-oxidation precursor solution. Specifically, the amount of the oxidant added is 1 times the molar amount of the transition metal ions in the solution; the oxidant is hydrogen peroxide or oxygen.

[0040] S3. Preparation of an ionic mixture: Add a phosphorus source to the above-mentioned pre-oxidation precursor solution to form a uniform ionic mixture. Specifically, the phosphorus source is pyrophosphoric acid or polyphosphoric acid.

[0041] S4. Preparation of precursor powder: Dry the ionic mixture to remove moisture and obtain dry precursor powder. Specifically, the drying method is high-temperature pyrolysis and forced air drying.

[0042] S5, high temperature calcination: calcining the above precursor powder at high temperature, and then cooling naturally to obtain M x PO y mH2O material. Specifically, the high-temperature calcination temperature is 400°C.

[0043] Example 3 This embodiment relates to a precursor for a high-density polyanion sodium ion battery positive electrode material. The precursor has the general chemical formula M x PO y mH2O, where M is the transition metal element Fe and Mn, and the range of values ​​of x, y, and m is 0.4 <x<1,y=3.5 / 3.75;m≥0。

[0044] The precursor was prepared by the following method: S1. Preparation of a precursor solution: A transition metal source and an organic acid are wet-mixed in a molar ratio of 1:5-15, and the reaction is controlled at 70°C to form a precursor solution. Specifically, the transition metal source is an iron source and a manganese source. The iron source is ferroferric oxide, ferric hydroxide, ferrous oxyhydroxide, ferrous hydroxide, ferrous citrate, or ferric oxalate. The manganese source is elemental manganese, manganese monoxide, or manganese dioxide. The organic acid is citric acid, malic acid, or ascorbic acid.

[0045] S2. Preparation of a pre-oxidation precursor solution: An oxidant is added to the above solution to oxidize the divalent metal ions in the solution to trivalent metal ions, thereby generating a pre-oxidation precursor solution. Specifically, the amount of the oxidant added is 2.5 times the molar amount of the transition metal ions in the solution; the oxidant is hydrogen peroxide.

[0046] S3. Preparation of an ionic mixture: Add a phosphorus source to the pre-oxidation precursor solution to form a uniform ionic mixture. Specifically, the phosphorus source is metaphosphoric acid or polyphosphoric acid.

[0047] S4. Preparation of precursor powder: Dry the above ionic mixture to remove water to obtain dry precursor powder. Specifically, the drying method is freeze drying or forced air drying.

[0048] S5, high temperature calcination: calcining the above precursor powder at high temperature, and then cooling naturally to obtain M x PO y mH2O material. Specifically, the high-temperature calcination temperature is 300°C.

[0049] Example 4 This embodiment relates to a precursor for a high-density polyanion sodium ion battery positive electrode material. The precursor has the general chemical formula M x PO y mH2O, where M is the transition metal element Fe, and the range of values ​​of x, y, and m is 0.4 <x<1,y=3.5 / 3.75;m≥0。

[0050] The precursor was prepared by the following method: S1. Preparation of a precursor solution: A transition metal source and an organic acid are wet-mixed in a molar ratio of 1:8 and reacted at 100°C to form a precursor solution. Specifically, the transition metal source is an iron source, which may be elemental iron, red iron oxide, ferrous oxide, ferroferric oxide, ferric hydroxide, ferrous oxyhydroxide, or ferrous hydroxide; and the organic acid is formic acid, acetic acid, citric acid, malic acid, or ascorbic acid.

[0051] S2. Preparation of a pre-oxidation precursor solution: An oxidant is added to the above solution to oxidize the divalent metal ions in the solution to trivalent metal ions, thereby generating a pre-oxidation precursor solution. Specifically, the amount of the oxidant added is 1-2.5 times the molar amount of the transition metal ions in the solution; the oxidant is peracetic acid or oxygen.

[0052] S3. Preparation of an ionic mixture: Add a phosphorus source to the above-mentioned pre-oxidation precursor solution to form a uniform ionic mixture. Specifically, the phosphorus source is phosphoric acid or pyrophosphoric acid.

[0053] S4. Preparation of precursor powder: Dry the ionic mixture to remove moisture and obtain dry precursor powder. Specifically, the drying method is forced air drying or natural evaporation.

[0054] S5, high temperature calcination: calcining the above precursor powder at high temperature, and then cooling naturally to obtain M x PO y mH2O material. Specifically, the high-temperature calcination temperature is 250°C.

[0055] Example 5 This embodiment relates to a precursor for a high-density polyanion sodium ion battery positive electrode material. The precursor has the general chemical formula M x PO y mH2O, where M is the transition metal element Mn, and the range of values ​​of x, y, and m is 0.4 <x<1,y=3.5 / 3.75;m≥0。

[0056] The precursor was prepared by the following method: S1. Preparation of a precursor solution: A transition metal source and an organic acid are wet-mixed in a molar ratio of 1:12 and reacted at 110°C to form a precursor solution. Specifically, the transition metal source is a manganese source, which may be elemental manganese, manganese monoxide, manganese dioxide, or manganese trioxide; and the organic acid is formic acid, acetic acid, citric acid, or malic acid.

[0057] S2. Preparation of a pre-oxidation precursor solution: An oxidant is added to the above solution to oxidize the divalent metal ions in the solution to trivalent metal ions, thereby generating a pre-oxidation precursor solution. Specifically, the amount of the oxidant added is twice the molar amount of the transition metal ions in the solution; the oxidant is hydrogen peroxide, peracetic acid, or oxygen.

[0058] S3. Preparation of an ionic mixture: Add a phosphorus source to the pre-oxidation precursor solution to form a uniform ionic mixture. Specifically, the phosphorus source is metaphosphoric acid or polyphosphoric acid.

[0059] S4. Preparation of precursor powder: Dry the ionic mixture to remove moisture to obtain dry precursor powder. Specifically, the drying method is spray drying.

[0060] S5, high temperature calcination: calcining the above precursor powder at high temperature, and then cooling naturally to obtain M x PO y mH2O material. Specifically, the high-temperature calcination temperature is 350°C.

[0061] Application Example 1 Fe 0.7275 PO 3.75 Preparation of 0.01H2O precursor and Na4Fe 2.91 Synthesis and electrochemical properties of (PO4)2P2O7 materials Step 1: High-purity iron powder and formic acid are mixed with water in a molar ratio of 1:10, and heated at 100°C to react to generate a transparent green solution; Step 2: Slowly add hydrogen peroxide to the green solution in an amount of 1.5 times the molar amount of iron ions in the solution to oxidize the divalent iron ions in the solution to trivalent iron ions, thereby generating a pre-oxidation precursor solution; Step 3: Add phosphoric acid to the pre-oxidation precursor solution in an amount of 5.15 times the molar amount of iron ions in the solution to form a uniform ionic mixture; Step 4: Spray dry the ionic mixture at an inlet air temperature of 300°C and an outlet air temperature of 100°C to remove moisture and obtain a dry precursor powder; Step 5: calcine the precursor powder at a high temperature to remove volatile carbon, hydrogen, oxygen and other components in the powder, and at the same time deoxidize and condense the phosphate to form pyrophosphate, and obtain Fe after natural cooling. 0.7275 PO 3.75 0.01H2O material; Fe 0.7275 PO 3.75 0.01H2O precursor, sodium acetate in a molar ratio of 1:4 and citric acid (the amount added is 0.2 times the molar amount of sodium acetate) were mixed and ground for about 0.1h. Compared with the anhydrous FePO4 precursor in comparative example 1, the grinding time was greatly reduced. The main reason is that Fe 0.7275 PO 3.75 The 0.01H2O precursor is a low-temperature sintering phase with low particle crystallinity, weak ionic bonding energy, and easy grinding. When the solid particle size Dmax in the slurry is ≤30nm, the slurry is spray-dried with an inlet air temperature of 300°C and an outlet air temperature of 90°C to remove moisture and obtain a dry precursor powder. Finally, the precursor powder is calcined at 600°C for 10 hours in a nitrogen atmosphere and then cooled naturally to obtain Na4Fe 2.91 (PO4)2P2O7 material.

[0062] Figure 1 Na4Fe 2.91The SEM of (PO4)2P2O7 material shows a regular spherical morphology, and the particle surface is relatively smooth, with high density and no obvious pores, indicating that the material has a high degree of solidity and high density. In addition, the results in Table 1 show that the porosity of the material is 1.5%, which is much lower than that of Comparative Example 1. This is consistent with the densification characteristics of the material mentioned above. Finally, the material shows a high compaction density of about 2.39g / cm 3 In addition, the XRD diffraction curve refinement calculation further proves that the phase purity of the material is as high as 99.3%, which is much higher than that of comparative example 1 (78.4%), indicating that Fe 0.7275 PO 3.75 The non-bonded state between elements in the 0.01H2O precursor facilitates uniform mixing of elements during subsequent grinding, promoting uniform nucleation of the material during sintering, making its crystallinity more complete and its phase purity higher.

[0063] Will Na4Fe 2.91 (PO4)2P2O7 Materials , SurP, PVDF5130 were added in a mass ratio of 9.5:0.2:0.3 NMP mixing, use a high-speed homogenizer to mix the above materials evenly to form a black slurry with uniform color and high fluidity, Of The black slurry was then coated onto aluminum foil using a 150 μm four-sided film preparation device and dried in a vacuum drying oven at 100°C for 2 hours. A sheet puncher was used to punch the electrode film into discs with a radius of 0.6 mm. CR2016 button cells were assembled in a glove box using sodium metal as the counter electrode, 1 mol / L NaClO₄EC+DEC (1:1 vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer separator.

[0064] The electrochemical performance test results in Table 1 show that Na4Fe 2.91The (PO4)2P2O7 electrode has a discharge capacity of 125.4 mAh / g at a rate of 0.1C (1C=129 mAh / g), which is much higher than the discharge capacity of 98.2 mAh / g in Comparative Example 1. This is related to the higher phase purity of the material, indicating that there are fewer unfavorable factors such as vacancies, defects, and dislocations in the material that restrict the capacity, thereby achieving high capacity performance. In addition, Table 1 shows that the capacity retention rate of the electrode at a rate of 10C is as high as 98.2% compared with 0.1C, which is much higher than 78.6% in Comparative Example 1. The reason is related to the high phase purity of the material. The higher the phase purity of the material, the higher the integrity of the primary grains, the fewer the grain boundaries between the grains, the lower the resistance to sodium ion migration, and the significantly improved rate performance. Finally, the electrode has a capacity retention rate of 99.1% after 1000 cycles at a rate of 1C, with almost no attenuation. The high capacity retention rate is related to the material's low porosity, which, to a certain extent, reduces side reactions at the electrolyte-material interface, effectively reducing ion dissolution and thereby improving structural stability. Furthermore, the material's high phase purity reduces the content of grain boundaries, resulting in more uniform volume expansion during repeated sodium ion insertion and extraction, and less particle degradation, which contributes to improved cycling stability.

[0065] Application Example 2 Mn 0.5 PO 3.5 Preparation of 0.03H2O precursor and synthesis and electrochemical performance of Na2MnP2O7 material Step 1: Mn2O3 and formic acid are mixed with water in a molar ratio of 1:14, and heated at 120°C to react to generate a transparent brown solution; Step 2: Slowly add hydrogen peroxide to the above brown solution in an amount of 1.9 times the molar amount of manganese ions in the solution to oxidize the manganese ions in the solution to generate a pre-oxidation precursor solution; Step 3: Add pyrophosphoric acid to the above pre-oxidation precursor solution in an amount of 0.5 times the molar amount of manganese ions in the solution to form a uniform ionic mixture; Step 4: Flash dry the above ionic mixture at a flash heating temperature of 280°C to remove moisture and obtain a dry precursor powder; Step 5: calcining the above precursor powder at a high temperature to remove volatile carbon, hydrogen, oxygen and other components in the powder, and at the same time further deoxidize and condense a small amount of phosphate in the solution to form pyrophosphate, and obtain Mn after natural cooling. 0.5 PO 3.5 ·0.03H2O material; Mn 0.5 PO 3.5A 0.03H2O precursor, sodium acetate, and glucose (added in an amount equal to 0.2 times the molar amount of sodium acetate) were mixed and ground with water in a molar ratio of 1:2 for approximately 0.15 hours. This grinding time and energy consumption were significantly lower than those in Comparative Example 2, resulting in lower process costs. When the solid particle size Dmax in the slurry was ≤30 nm, the slurry was spray-dried at an inlet air temperature of 300°C and an outlet air temperature of 100°C to remove moisture and obtain a dry precursor powder. Finally, the precursor powder was calcined at 650°C for 12 hours in a nitrogen atmosphere and allowed to cool naturally to obtain the Na2MnP2O7 material.

[0066] The results in Table 1 show that the porosity of Na2MnP2O7 material is 1.1%, which is much lower than that of Comparative Example 2. This is related to the low particle size distribution of the material precursor during the grinding process, which will increase the degree of local ion melting and bonding during the sintering process, making the formed material particles denser, the particle growth more dense, the porosity lower, and the compaction density increased (2.27g / cm 3 ). XRD diffraction curve refinement calculation further proves that the phase purity of the material is as high as 99.8%, which is much higher than that of comparative example 2 (79.2%), indicating that Mn 0.5 PO 3.5 The uniform distribution of elements in the 0.03H2O precursor can effectively promote the growth of crystals during sintering. By shortening the ion diffusion distance during sintering, it makes it easier for crystallization to nucleate, forming a material with high crystallinity and high phase purity.

[0067] Will Na2MnP2O7 material , SurP, PVDF5130 were mixed with NMP in a mass ratio of 9.5:0.2:0.3. Use a high-speed homogenizer to mix the above materials evenly to form a black slurry with uniform color and high fluidity. The black slurry was then coated onto aluminum foil using a 150 μm four-sided film preparation device and dried in a vacuum drying oven at 100°C for 2 hours. A sheet puncher was used to punch the electrode film into discs with a radius of 0.6 mm. CR2016 button cells were assembled in a glove box using sodium metal as the counter electrode, 1 mol / L NaClO₄EC+DEC (1:1 vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer separator.

[0068] The electrochemical performance test results in Table 1 show that the electrode has a discharge capacity of 115.1 mAh / g at a rate of 0.1C (1C = 120 mAh / g), and its capacity is relatively high. This is related to the higher phase purity of the material. The higher the phase purity, the more redox charges in its structure, which is more conducive to the high capacity of the material. In addition, Table 1 shows that the capacity retention rate of the electrode at a rate of 10C is as high as 96.5% compared with 0.1C, which is much higher than 35.4% in Comparative Example 2. This shows that the higher the phase purity of the material, the fewer crystal defects and grain boundaries, the lower the diffusion energy barrier of sodium ions in the structure, and the faster the ion transport rate, which is more conducive to the improvement of its rate performance. Finally, the electrode has a capacity retention rate of 95.9% after 1000 cycles at a rate of 1C, showing excellent cycle stability. This shows that the higher the phase purity of the material, the better the crystal integrity, the higher the isotropy of the crystal expansion, the lower the pulverization rate of the interface structure, and the better the cycle stability. In addition, the smaller specific surface area of ​​this material will, to a certain extent, reduce its catalysis of the electrolyte under high voltage, thereby reducing side reactions at the material interface and improving its cycle stability.

[0069] Comparative Example 1 Preparation of Na4Fe from anhydrous FePO4 precursor 2.91 (PO4)2P2O7 Materials and Their Electrochemical Properties Anhydrous FePO4, phosphoric acid, and sodium acetate are mixed with water in a molar ratio of 2.91:1.0:4.0 and citric acid (the amount added is 0.2 times the molar amount of sodium acetate) for about 10 hours. The grinding time is longer than that of Application Example 1, the energy consumption is larger, the equipment investment is large, and the cost is high. When the particle size of the solid particles in the slurry Dmax ≤ 30nm, the slurry is spray-dried with an air inlet temperature of 300°C and an air outlet temperature of 90°C to remove moisture and obtain a dry precursor powder. Finally, the above-mentioned precursor powder is calcined at 600°C for 10 hours in a nitrogen atmosphere, and Na4Fe is obtained after natural cooling. 2.91 (PO4)2P2O7 material.

[0070] Figure 2 Na4Fe 2.91 The SEM of the (PO4)2P2O7 material shows that it is composed of primary particles of about 50-100nm, with a large number of pores on the particles and a low particle density. The results in Table 1 show that the porosity of the material is 17.9%, which is much higher than that of Application Example 1. This is related to the anhydrous FePO4 precursor. The precursor is a high-temperature sintered phase, and its particles are hard and have many edges and corners after grinding. These particles stack on each other during the spraying process to form a porous spherical arrangement. The pores are not removed after sintering, resulting in an increase in its porosity and a decrease in the compacted density (1.96g / cm 3). XRD diffraction curve refinement calculation further proves that the phase purity of the material is only 78.4%, which is much lower than that of Application Example 1. This shows that it is difficult to achieve uniform mixing between ions in the FePO4 precursor during the grinding process, which easily causes the generation of impurities during the sintering process, affecting the phase purity of the material.

[0071] Will Na4Fe 2.91 (PO4)2P2O7 Materials , SurP, PVDF5130 were added in a mass ratio of 9.5:0.2:0.3 NMP mixing, use a high-speed homogenizer to mix the above materials evenly to form a black slurry with uniform color and high fluidity, Of The black slurry was then coated onto aluminum foil using a 150 μm four-sided film preparation device and dried in a vacuum drying oven at 100°C for 2 hours. A sheet puncher was used to punch the electrode film into discs with a radius of 0.6 mm. CR2016 button cells were assembled in a glove box using sodium metal as the counter electrode, 1 mol / L NaClO₄EC+DEC (1:1 vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer separator.

[0072] The results in Table 1 show that the discharge capacity of the material at a rate of 0.1C (1C=129mAh / g) is only 90.3mAh / g, which is much lower than the discharge capacity of the material in Application Example 1. This is consistent with the low phase purity of the material, indicating that the material prepared with anhydrous FePO4 as a precursor may contain impurities such as inactive sodium iron phosphate or low-capacity sodium iron pyrophosphate, which reduces the effective active ingredients of the material per unit mass, reduces the number of transition metal redox and sodium ion deintercalation, and reduces the material capacity. In addition, Table 1 shows that the capacity retention rate of the electrode at a rate of 10C is only 78.6% compared with that at 0.1C. The low rate performance is related to the presence of impurities in the material. The grain boundaries between phases will hinder the transmission of sodium ions, which in turn leads to a decrease in the rate performance of the material. Finally, at a rate of 1C, after 1000 cycles, the capacity retention rate of the electrode is only 88.6%, which is a serious attenuation. The reason is that during the sodium deintercalation process, Na4Fe 2.91 The different volume expansion rates of different phases in the (PO4)2P2O7 material are different, resulting in problems such as material pulverization at the grain boundaries, affecting the integrity of the structure. On the other hand, the large number of pores in the material will cause the interface to react with the electrolyte under high voltage, and the ion dissolution at the material interface will be aggravated, affecting the cyclic stability of the material. In summary, the Na4Fe prepared with anhydrous FePO4 precursor 2.91 The heterogeneity of the material reaction caused by the low phase purity and high porosity of (PO4)2P2O7 material will accelerate the degradation of the electrochemical performance of the material.

[0073] Comparative Example 2 Preparation of Na2MnP2O7 Material from Mn2O3 Precursor and Its Electrochemical Properties Mn2O3, pyrophosphoric acid, and sodium acetate were mixed with water and ground in a molar ratio of 0.5:1.0:2.0 with glucose (added in an amount 0.2 times the molar amount of sodium acetate) for about 18 hours. The grinding time was longer than that in Application Example 2. The main reason was that Mn2O3 had a high crystallinity and a large crystal hardness, which made it difficult to grind. This resulted in large process energy consumption, reduced efficiency, and high cost investment. When the solid particle size Dmax in the slurry was ≤30nm, the slurry was spray-dried with an inlet air temperature of 300°C and an outlet air temperature of 100°C to remove moisture and obtain a dry precursor powder. Finally, the precursor powder was calcined at 650°C for 12 hours in a nitrogen atmosphere, and the Na2MnP2O7 material was obtained after natural cooling.

[0074] The physical and chemical test data in Table 1 show that the porosity of the material is 15.4%, which is much higher than that of Application Example 2. This is related to the Mn2O3 precursor. This type of precursor is a high-temperature sintered phase, and its particles are hard. After grinding, there are many edges and corners. After spray drying, they are stacked on each other to form a porous structure. These pores are not removed after sintering, resulting in an increase in its porosity and specific surface area, and a decrease in the compacted density (1.79 g / cm 3 ). XRD diffraction curve refinement calculations further prove that the phase purity of the material is only 79.2%, which is much lower than that of Application Example 2. This indicates that the Mn2O3 precursor grains are relatively hard and difficult to grind into powder, which is not conducive to uniform mixing of ions during the grinding process, resulting in phase separation during the sintering process, affecting the material's crystal structure and phase purity.

[0075] Will Na2MnP2O7 material , SurP, PVDF5130 were mixed with NMP in a mass ratio of 9.5:0.2:0.3. Use a high-speed homogenizer to mix the above materials evenly to form a black slurry with uniform color and high fluidity. The black slurry was then coated onto aluminum foil using a 150 μm four-sided film preparation device and dried in a vacuum drying oven at 100°C for 2 hours. A sheet puncher was used to punch the electrode film into discs with a radius of 0.6 mm. CR2016 button cells were assembled in a glove box using sodium metal as the counter electrode, 1 mol / L NaClO₄EC+DEC (1:1 vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer separator.

[0076] The results in Table 1 show that the discharge capacity of the material at a rate of 0.1C (1C = 120mAh / g) is only 69.8mAh / g, which is much lower than the results in Application Example 2. This is related to the low phase purity of the material mentioned above, indicating that the material prepared with Mn2O3 as a precursor may produce other impurities due to uneven mixing between elements, resulting in a decrease in the material's specific capacity. In addition, Table 1 shows that the capacity retention rate of the electrode at a rate of 10C is only 35.4% compared to that at 0.1C. The low rate performance is related to the presence of a large number of grain boundaries between the phases, which will reduce the sodium ion transmission rate and lead to a decrease in the rate performance of the material. Finally, at a rate of 1C, after 1000 cycles, the capacity retention rate of the electrode is only 76.3%, which is severely attenuated, indirectly reflecting the instability of the material structure. The reason is related to the high specific surface area of ​​the material, which catalyzes the reaction of the electrolyte at high voltage, leading to problems such as interface dissolution and structural lithification, affecting the cyclic stability of the material.

[0077] Table 1 Performance test results The above embodiments are merely specific embodiments of the present invention, and their descriptions are relatively specific and detailed. However, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make various modifications and improvements without departing from the scope of the present invention, and such obvious alternatives are all within the scope of protection of the present invention.

Claims

1. A precursor for a high-density polyanion sodium ion battery cathode material, characterized in that: The precursor chemical formula is M x PO y mH2O, where M is the transition metal element Fe and / or Mn, and the range of values ​​of x, y, and m is 0.4 <x<1,y=3.5 / 3.75;m≥0。 2. A method for preparing a precursor for a high-density polyanion type sodium ion battery positive electrode material, characterized in that The following steps are involved: S1. Preparation of precursor solution: wet mixing the transition metal source and the organic acid, and reacting them at a controlled temperature to generate a precursor solution; S2. Preparation of a pre-oxidation precursor solution: adding an oxidant to the above solution to oxidize the divalent metal ions in the solution into trivalent metal ions to generate a pre-oxidation precursor solution; S3, preparation of an ionic mixture: adding a phosphorus source to the above-mentioned pre-oxidation precursor solution to form a uniform ionic mixture; S4, preparation of precursor powder: drying the above ionic mixture to remove water to obtain dry precursor powder; S5. High temperature calcination: calcine the above precursor powder at high temperature, and then cool down naturally to obtain M x PO y mH2O material.

3. The method for preparing a precursor for a high-density polyanion type sodium ion battery positive electrode material according to claim 2, characterized in that: In step S1, the molar ratio of the transition metal source to the organic acid is 1:5-15.

4. The precursor for the positive electrode material of a high-density polyanion sodium ion battery according to claim 2, characterized in that: In step S1, the temperature of the temperature-controlled reaction is 70-120°C.

5. The high-density polyanion sodium ion battery positive electrode material precursor according to claim 2, characterized in that: In step S2, the amount of the oxidant added is 1-2.5 times the molar amount of the transition metal ions in the solution.

6. The method for preparing a precursor for a high-density polyanion type sodium ion battery positive electrode material according to claim 2, characterized in that: In step S5, the temperature of high temperature calcination is 150-400°C.

7. The method for preparing a precursor for a high-density polyanion type sodium ion battery positive electrode material according to claim 2, characterized in that: In step S2, the oxidant is one or more of hydrogen peroxide, peracetic acid, and oxygen.

8. The precursor for the positive electrode material of a high-density polyanion sodium ion battery according to claim 7, characterized in that: In step S1, the transition metal source is an iron source and / or a manganese source, the iron source is one or more of elemental iron, red iron oxide, ferrous oxide, ferric oxide, ferric hydroxide, ferrous oxyhydroxide, ferrous hydroxide, ferric citrate, and ferric oxalate, the manganese source is one or more of elemental manganese, manganese monoxide, manganese dioxide, manganese trioxide, manganese tetraoxide, manganese oxalate, manganese hydroxide, manganous anhydride, manganic anhydride, and permanganic anhydride; the organic acid is one or more of formic acid, acetic acid, citric acid, malic acid, ascorbic acid, tartaric acid, and salicylic acid.

9. The method for preparing a precursor for a high-density polyanion type sodium ion battery positive electrode material according to claim 2, characterized in that: In step S3, the phosphorus source is one or more of phosphoric acid, pyrophosphoric acid, metaphosphoric acid, and polyphosphoric acid.

10. The method for preparing a precursor for a positive electrode material for a high-density polyanion sodium ion battery according to claim 2, characterized in that: In step S4, the drying method is one or more of flash drying, spray drying, high temperature cracking, freeze drying, forced air drying, and natural evaporation.

Citation Information

Patent Citations

  • Preparation method of polyanionic sodium ion battery positive electrode material

    CN117585659A

  • Polyanionic sodium ion battery positive electrode material precursor and preparation method thereof

    CN118479443A

  • Preparation method and application of ferric manganese phosphate precursor

    CN118619236A

  • Amorphous disordered precursor for polyanionic sodium ion battery positive electrode material and preparation method of amorphous disordered precursor

    CN118833790A